ANALYSIS OF THE RELATIONSHIP BETWEEN ESG VALUES AND FINANCIAL PERFORMANCE AND MARKET VALUE OF COMPANIES IN THE MINING SECTOR: A CASE STUDY OF MINING COMPANIES LISTED ON ASIAN STOCK EXCHANGES - Azmi Haryono, Muhammad
In recent decades, there has been an increasing focus on non-financial aspects, such as ESG, in evaluating corporate performance. This study aims to analyze the impact of ESG scores on firm value, measured through Tobin's Q and (PBV), across several mining companies in Asia. The study employs panel data regression analysis to evaluate the relationship between ESG scores and market value, while also exploring the variation of this impact across different countries, including Indonesia, Malaysia, Turkey, South Korea, and Taiwan. The results indicate that ESG scores have a significant impact on firm value in Asia. Generally, an increase in ESG scores tends to negatively correlate with Tobin's Q and PBV, suggesting that markets in Asia may still view ESG investments as an additional burden that does not necessarily provide short-term financial gains. However, this impact varies significantly across countries. In Indonesia, the negative impact of ESG on firm value is relatively moderate, while in Malaysia and Turkey, the impact is more pronounced. Conversely, in South Korea and Taiwan, an increase in ESG scores has a slightly positive effect on firm value. The study concludes that while ESG is an important component of corporate sustainability, its implementation needs to be adapted to the local context to achieve optimal results in enhancing market value.